Observation Study among Cured Cases of Pulmonary Tuberculosis: A Long-Term Study under the Revised National Tuberculosis Control Program - Anil K Agarwal; Divyani Aharwal; Rani Verma; Ramniwas Mahore; Priyanka Kushwaha (Masters Program in Public Health, 2023)
Background: Tuberculosis is one of the leading causes of mortality in India. The Revised National Tuberculosis Control Program (RNTCP) is a robust public health system to deal with Tuberculosis (TB) in India. Unless the treated patient comes back to the system with signs and symptoms of TB due to relapse or reinfection, there is no mechanism of follow-up or any method to know the relapse rate in the population. This study aimed to analysed trends in relapse tuberculosis cases and describe their associations with socio-demographic and clinical factors.Subjects dan Method: In this prospective cohort study, 750 selected sample size who were declared “Cured” in four randomly selected TB units of Gwalior district were followed up for 1–5 years through home visits by trained staff with structured data collection forms. Data Collection was done between January 2022 to June 2022 and afterwards analyzed using Microsoft excel spreadsheet.Results: The mean age of the index cases was Mean= 30.53; SD= 14.24 years, and there were 39 females and 64 males. At early stage (1-to-2-year posttreatment follow-up of 248 index cases) 199 (80.2%) were healthy and working without any symptoms of TB. Symptoms of TB were present in 49 (19.8%) cases. The after 2-year posttreatment TB Symptoms were present in 54 (19.3%) cases.Conclusion: Long-term follow-up of cured, new smear-positive TB cases reinforce the effectiveness of anti-TB treatment under the RNTCP as assessed by improved health outcomes in more than two-thirds of cases and posttreatment survival of 80.72% of index cases. Further investigation needed to continue such follow-up for all TB cases treated under the RNTCP for effective end-TB strategy. Keywords: tuberculosis treatment, follow-up, relapses, RNTCP Correspondence: Ramniwas Mahore. Department Of Community Medicine. G R Medical College Gwalior 474009 Madhya Pradesh, India. Email: Drmahore@gmail.com. Mobile: 9425334365.